Petrogenesis and Geodynamic Implications of Late Triassic Mogetong Adakitic Pluton in East Kunlun Orogen, Northern Tibet: Constraints from Zircon U–Pb–Hf Isotopes and Whole-Rock Geochemistry - Gan, Jie; Xiong, Fuhao; Xiao, Qianru; Wang, Wei; Yan, Dongdong (Frontiers in Earth Science, 2022)
Adakites or adakitic rocks usually showing special geochemical signatures, are petrological probes to reveal the tectono–magmatic evolutionary history of paleo–orogenic belts. Here, we present comprehensive studies on the zircon U–Pb geochronology, whole-rock geochemistry, and zircon Lu-Hf isotopes of Mogetong adakitic pluton in East Kunlun orogen, Northern Tibetan Plateau, to constrain its petrogenesis and tectonic setting, and thus to reveal its implications for the Paleo–Tethyan orogeny. The studied pluton comprises of quartz monzonite porphyry with zircon U–Pb crystallization age of ca. 215 Ma, which is coeval to their diorite enclaves (ca. 212 Ma). The quartz monzonite porphyries have intermediate SiO2 (63.31–65.74 wt.%), relatively high Al2O3 (15.52–16.02 wt.%), K2O (2.83–3.34 wt.%) and Sr (462–729 ppm), but low Y (9.14–15.7 ppm) and Yb (0.73–1.39 ppm) with high Mg# (47–55), Sr/Y (30–57) and La/Yb ratios, resembling typical high–K calc-alkaline and high Mg# adakitic rocks. Zircon Lu–Hf isotopes show that the studied samples have weakly juvenile zircon Lu-Hf isotopes (εHf(t) =1.80–4.03) with older model age (1.00–1.14 Ga). The relative low contents of Cr (14–59 ppm) and Ni (8–30 ppm), as well as the petrological, geochemical and Lu-Hf isotopic data, indicates that the Mogetong adakitic rocks were generated by partial melting of thickened lower crust with a certain contribution of the underplated mantle-derived magma in slab break-off setting. This study shows that the Late Triassic adakitic magmatism in East Kunlun orogen may be the response of tectonic transition from oceanic subduction to post–subduction extension, and the reworking of ancient continental crust with subsequent variable crust-mantle magma mixing is the major mechanism of continental crust evolution in Paleo–Tethyan orogenic belt.